2019
DOI: 10.3390/rs11101232
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Electromagnetic Properties of In Situ Soils for the Design of Landmine Detection Sensors: Application in Donbass, Ukraine

Abstract: To design holographic and impulse ground penetrating radar (GPR) sensors suitable for humanitarian de-mining in the Donbass (Ukraine) conflict zone, we measured critical electromagnetic parameters of typical local soils using simple methods that could be adapted to any geologic setting. Measurements were recorded along six profiles, each crossing at least two mapped soil types. The parameters selected to evaluate GPR and metal detector sensor performance were magnetic permeability, electrical conductivity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In this environment, the reading of the images acquired with the imaging system is more complex, as there are many degrading effects for the signal that significantly decrease the Signal-Noise ratio: the reflection of the ground surface and its surface irregularity which is of comparable size with the wavelength of the radar signal, they generate diffraction phenomena. The soil, which is a highly dispersive propagation medium, determines a strong attenuation of the signal [27][28][29].…”
Section: Antennae Field Testmentioning
confidence: 99%
“…In this environment, the reading of the images acquired with the imaging system is more complex, as there are many degrading effects for the signal that significantly decrease the Signal-Noise ratio: the reflection of the ground surface and its surface irregularity which is of comparable size with the wavelength of the radar signal, they generate diffraction phenomena. The soil, which is a highly dispersive propagation medium, determines a strong attenuation of the signal [27][28][29].…”
Section: Antennae Field Testmentioning
confidence: 99%
“…Thanks to this methodology, it was possible to detail a sharp change of material to 2.4 m, which is understood as the original rock or foundation of the wall at this point in the city, something that, until now, had not been known, and that greatly facilitates our the understanding of this unique In addition, a GPR study was carried out in order to refine the thicknesses of these layers and to control what was happening inside the wall-we were looking for holes and gaps that also explained the construction model followed for each material [23][24][25]. One of these radargramas it is shown in Figure 11, where the discontinuities in the wall can be seen.…”
Section: Second Phase-the Buildingmentioning
confidence: 99%
“…One of these radargramas it is shown in Figure 11, where the discontinuities in the wall can be seen. In addition, a GPR study was carried out in order to refine the thicknesses of these layers and to control what was happening inside the wall-we were looking for holes and gaps that also explained the construction model followed for each material [23][24][25]. One of these radargramas it is shown in Figure 11, where the discontinuities in the wall can be seen.…”
Section: Second Phase-the Buildingmentioning
confidence: 99%
“…There, Bechtel et al used a GPR for the electromagnetic characterization of soils and it was able to design suitable holographic impulse sensors. The authors indicated that the variation in electromagnetic properties was surprisingly small and within the normal range for most soils throughout the world [56]. About the development of holographic radar for the detection of landmines, Qin et al modeled a monostatic antenna with a fixed frequency to transmit and receive electromagnetic signals, considering the conditions of flat and sinusoidal surfaces.…”
Section: Analysis Of Explosive Compoundsmentioning
confidence: 99%